2015
DOI: 10.1016/j.ijimpeng.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

The mechanical response of a syntactic polyurethane foam at low and high rates of strain

Abstract: Quasi-static and dynamic experiments are conducted to characterise the mechanical response of a syntactic foam comprising hollow glass microballoons in a polyurethane matrix. Stress versus strain histories are measured in uniaxial tension and compression as well as in pure shear, at strain rates ranging from quasi-static in-situ tests are conducted to visualise the deformation mechanisms in tension and compression. The material displays a pronounced sensitivity to the imposed strain rate and relatively high te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 32 publications
2
47
0
1
Order By: Relevance
“…Recently, more research efforts have been made to explore the high strain rate response of the foam. [10,[12][13][14][15][16][17][18][19][20] Dynamic properties of syntactic foams are affected by the geometry and volume fraction of hollow microspheres. [13][14][15][16] The treatment of hollow microspheres can improve their interfacial adhesion to the epoxy matrix and thus the impact properties of the bulk foam, especially the strength.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, more research efforts have been made to explore the high strain rate response of the foam. [10,[12][13][14][15][16][17][18][19][20] Dynamic properties of syntactic foams are affected by the geometry and volume fraction of hollow microspheres. [13][14][15][16] The treatment of hollow microspheres can improve their interfacial adhesion to the epoxy matrix and thus the impact properties of the bulk foam, especially the strength.…”
mentioning
confidence: 99%
“…[10] Pellegrino et al reported the glass microballoon polyurethane syntactic foam possesses higher strain rate sensitivity in tension compared to compression. [17] However, very little research has focused on the microscopic failure mechanism of syntactic foams subjected to dynamic loads.…”
mentioning
confidence: 99%
“…Various different approaches have already been taken to understand macroscopic failure mechanisms in polymer/glass syntactic foams when subjected to different loading conditions [5][6][7][8][9][10]. It was found that crack directions (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Pellegrino et al [13][14][15] presented that the PU based syntactic foam's strain rate sensitivity was superior to that of solid PU and conventional PU foams of similar density. However, higher content of the bubbles worsen the compression properties owing to an increased amount of defects in the structure of the filled polyurethane [14].…”
Section: Introductionmentioning
confidence: 99%